2023
DOI: 10.1002/jcsm.13182
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Phosphoribosyltransferase‐elevated NAD+ biosynthesis prevents muscle disuse atrophy by reversing mitochondrial dysfunction

Abstract: Background It is well known that muscle disuse atrophy is associated with mitochondrial dysfunction, which is implicated in reduced nicotinamide adenine dinucleotide (NAD+) levels. Nicotinamide phosphoribosyltransferase (NAMPT), a rate‐limiting enzyme in NAD+ biosynthesis, may serve as a novel strategy to treat muscle disuse atrophy by reversing mitochondrial dysfunction. Methods To investigate the effects of NAMPT on the prevention of disuse atrophy of skeletal muscles predominantly composed of slow‐twitch (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The biosynthesis of NAD in humans is controlled by dimeric protein-based phosphoribosyl transferase (NAPRT, Type II) with the combined effort of quinoline phosphoribosyl transferase (QPRT) and NAMPT. It was revealed that NAPRT activity is not influenced by NAD as in the case of NAMPT [ 47 ]. The NAD regulation by NAPRT is specific to tissue and certain conditions [ 48 ].…”
Section: The Biological Significance Of Naprt In Cardiac Healthmentioning
confidence: 99%
“…The biosynthesis of NAD in humans is controlled by dimeric protein-based phosphoribosyl transferase (NAPRT, Type II) with the combined effort of quinoline phosphoribosyl transferase (QPRT) and NAMPT. It was revealed that NAPRT activity is not influenced by NAD as in the case of NAMPT [ 47 ]. The NAD regulation by NAPRT is specific to tissue and certain conditions [ 48 ].…”
Section: The Biological Significance Of Naprt In Cardiac Healthmentioning
confidence: 99%